Analisis Kualitas Produk, Harga Dan Brand Identity Terhadap Loyalitas Pelanggan Dengan Keputusan Pembelian Sebagai Variable Intervening - Aziz, Zaenal; Margono, Hery (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to determine the Influence of Product Quality, Price, and Brand Identity on Customer Loyalty both directly and indirectly through Customer Purchase Decision as a Product Intervening Variable The analysis method used (Structural Equation Modelling-Partial Equation Modelling) SEM-PLS using SmartPLS 4.0 software.The methodology used is a quantitative approach with data collection through questionnaire surveys distributed to t PT Dinamika Utama Pangan. The results show that product quality has a negative but significant effect on customer loyalty (-0.097), while price also shows a significant negative effect (-0.055). In contrast, brand identity has a significant positive effect on customer loyalty (0.290). Purchasing decisions proved to be an important factor that had a significant positive effect on customer loyalty (0.319).The relationship between product quality and purchase decision shows a significant positive effect (0.712), while price has a negative effect (-0.025) and brand identity has a significant positive effect (0.149). Mediation analysis shows that purchasing decisions significantly mediate the effect of product quality on customer loyalty (0.017), but are not significant in mediating the effect of price (0.077) or brand identity (0.713) on customer loyalty.